Pengaruh Net Interest Margin (Nim) Dan Biaya Operasional Pada Pendapatan Operasional (Bopo) Terhadap Harga Saham Pada Bank Bumn Yang Terdaftar Di Bei Periode 2016-2024 - Tiara Gita Safitri; Neneng Khoiriah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to obtain empirical evidence on the effect of Net Interest Margin (NIM) and Operating Expenses to Operating Income (BOPO) on stock prices of State-Owned Commercial Banks (Bank BUMN) listed on the Indonesia Stock Exchange (IDX) during the period 2016–2024. The population of this study consists of State-Owned Banks listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, which resulted in a sample of four State-Owned Banks. The data used in this study are secondary data obtained from annual financial statements and stock price data. The data analysis method employs descriptive statistical analysis, classical assumption tests, and hypothesis testing. EViews version 12 is used as the analytical tool. The results of the study indicate that partially, Net Interest Margin (NIM) has a positive and significant effect on stock prices, with a t-statistic value of 2.687620 greater than the t-table value of 1.69236 and a probability value of 0.0116. Meanwhile, Operating Expenses to Operating Income (BOPO) shows a t-statistic value of 1.4011332, which is lower than the t-table value of 1.69236 with a probability value of 0.1714, indicating that BOPO does not have a significant effect on stock prices. Simultaneously, Net Interest Margin (NIM) and Operating Expenses to Operating Income (BOPO) have a significant effect on stock prices, as indicated by an F-statistic value of 13.90776 greater than the F-table value of 3.280 and a probability value of 0.000000. Therefore, it can be concluded that NIM and BOPO simultaneously influence stock prices of State-Owned Banks listed on the Indonesia Stock Exchange during the period 2016–2024 Keywords: Stock Price, Net Interest Margin (NIM), Operating Expenses to Operating Income (BOPO)